Effect of post AI intrauterine treatment with E. coli lipopolysachharide and autologous serum on characteristics of cervico-vaginal mucous in subclinical endometritic cows
Sub-clinical bacterial endometritis is a common cause of repeat-breeding in cows. The present study was conducted on 36 cows with confirmed sub-clinical endometritis. Based on the treatment protocol, these cows were divided randomly into three groups of 12 animals each. Group 1 (control